Cash flow, corporate governance, corporate social responsibility on financial performance - Agustina, Yumniati; Setiadi, Iwan; Sudrajat, Endrawan (Trigin Publisher, 2024)
This study aims to analyze the influence of Operating Cash Flow, the Implementation of Good Corporate Governance (GCG), and Corporate Social Responsibility (CSR) Practices on the Financial Performance of Mining Sector Companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sample consists of 20 mining companies, totaling 100 data points, determined using the purposive sampling method. This quantitative research employs associative quantitative analysis in a causal relationship framework, utilizing secondary data with a ratio scale, processed through SPSS version 26. Data analysis techniques include descriptive statistics, classical assumption tests, model tests (multiple linear regression), and hypothesis tests. The findings indicate that, partially, Cash Flow, Institutional Ownership, and Managerial Ownership have a positive and significant impact on Financial Performance, while the Independent Board of Commissioners and Corporate Social Responsibility do not significantly affect Financial Performance. Collectively, Cash Flow, Institutional Ownership, Managerial Ownership, Independent Board of Commissioners, and Corporate Social Responsibility significantly influence Financial Performance, accounting for 74.0% of the variance, with the remaining 26.0% influenced by variables not included in this study